4‐Fluoroamphetamine (4‐FA) intoxication results in exaggerated blood pressure effects compared to MDMA and amphetamine: A retrospective analysis. Issue 5 (26th September 2022) - Gresnigt, Femke M. J.; Snik, Anouk; Franssen, Eric J. F.; Vanhommerig, Joost W.; de Lange, Dylan W.; Riezebos, Robert K.
Abstract: Objective: 4‐Fluoroamphetamine (4‐FA) is an amphetamine‐type stimulant, with effects comparable to amphetamine and 3, 4‐methylenedioxymethamphetamine (MDMA). Severe 4‐FA‐related complications, such as cardiomyopathy, myocardial infarction, and cerebral hemorrhage, have been described. The aim of this study was to explore the cardiovascular symptoms and complications in 4‐FA and compare them to MDMA and amphetamine in intoxicated patients who presented to the emergency department (ED). Methods: Between November 2015 and March 2020, all self‐reported 4‐FA, MDMA, and amphetamine‐intoxicated adult patients that presented at the ED of an inner‐city hospital in Amsterdam, were retrospectively analyzed for cardiovascular symptoms, vital parameters, cardiovascular complications, interventions, admission rate, and Poisoning Severity Score (PSS). Results: A total of 582 patients were included, of which 31 (5.3%) with 4‐FA intoxication (10/31 mono‐intoxications, 32.3%), 406 (69.8%) with MDMA (59/406 mono‐intoxications, 14.5%), 100 (17.2%) with amphetamine (10/100 mono‐intoxications, 10.0%), and 45 (7.7%) with a cross intoxication of these drugs. 4‐FA mono‐intoxicated patients experienced more headache (n = 8; 80.0%) compared to MDMA (n = 2; 3.3%; P < 0.001) and amphetamine mono‐intoxicated patients (n = 0; 0.0%; P < 0.001) and their systolic blood pressure was higher (164 mm Hg ± 31 vs 139 mm Hg ± 19; P = 0.031 vs 135 mm Hg ± 22; P = 0.033, respectively). Severe 4‐FA‐related cardiovascular complications included Takotsubo cardiomyopathy (n = 1; 3.2%), subarachnoid hemorrhage (n = 1; 3.2%), and hypertensive urgency (n = 2; 6.5%). Conclusions: 4‐FA intoxication‐related ED symptoms resemble MDMA and amphetamine complications, although patients presented more often with headache and hypertension. Severe 4‐FA‐related cardiovascular complications occurred in 40% of mono‐intoxications.